Generalised pustular onychopathy of unknown aetiology in a domestic cat. Issue 2 (20th December 2022) - Luciani, Luca; Legnani, Sara; Brachelente, Chiara
Abstract: Claw diseases are rare in cats and often associated with cutaneous lesions in other regions of the body. This case report describes an atypical manifestation of a generalised onychopathy of unknown origin in a domestic short hair cat. Abstract : Claw diseases are rare in cats and often associated with cutaneous lesions in other regions of the body. This case report describes an atypical manifestation of a generalised onychopathy of unknown origin in a domestic short hair cat. Résumé: Les maladies des griffes sont rares chez le chat et souvent associées à des lésions cutanées dans d'autres régions du corps. Ce rapport de cas décrit une manifestation atypique d'une onychopathie généralisée d'origine inconnue chez un chat domestique à poils courts. Resumen: Las enfermedades de las uñas son raras en los gatos y, a menudo, se asocian con lesiones cutáneas en otras regiones del cuerpo. Este artículo describe un caso de una manifestación atípica de onicopatía generalizada de origen desconocido en un gato doméstico de pelo corto. Zusammenfassung: Krallenkrankheiten kommen bei Katzen selten vor und treten oft im Zusammenhang mit kutanen Veränderungen in anderen Körperregionen auf. Dieser Fallbericht beschreibt eine atypische Manifestation einer generalisierten Onychopathie unbekannten Ursprungs bei einer Kurzhaarkatze. 要約」: 爪疾患は猫では稀であり、しばしば体の他の部位に皮膚病変を伴う。本症例は、ドメスティック・ショートヘアー・キャットの原因不明の爪疾患の非典型的な症状について述べたものである。 摘要: 爪病在猫中很少见，并且常与身体其他区域的皮肤病变有关。本病例报告描述了一只家养短毛猫中不明原因的多发性趾甲病的非典型表现。 Resumo: Enfermidades ungueais em gatos são raras, e muitas vezes são associadas a lesões cutâneas em outras regiões do corpo. Este caso descreve uma manifestação atípica de uma onicopatia generalizada de origem desconhecida em um gato doméstico de pelo curto.